Impact of Financial Development on Economic Growth of Nepal - Karki, Samiksha; Pradhan, R. S. (Nepalese Journal of Economics, 2024)
This study examines the impact of financial development on economic growth of Nepal. The dependent variables are real gross domestic product and per capita income. The independent variables are money supply, stock market capitalization, private sector credit, financial access and net foreign direct investment inflows. The study is based on time series data for the period by Ministry of Finance and Central Bureau of Statistics of Nepal. The correlation coefficients and regression models are estimated to test the significance and importance of financial development on economic growth in Nepal.The study showed that stock market capitalization has a positive impact on real gross domestic product and per capita income. It indicates that higher the stock market capitalization, higher would be the real gross domestic product and per capita income. Similarly, there is a positive impact of private sector credit to GDP on real gross domestic product and per capita income. It indicates that increase in private sector credit leads to increase in real gross domestic product and per capita income. In addition, broad money supply has a positive impact on real gross domestic product and per capita income indicating that higher the broad money supply, higher would be the real gross domestic product and per capita income. Similarly, financial access has a positive impact on real gross domestic product and per capita income. It indicates that increase in financial access leads to increase in real gross domestic product and per capita income. Likewise, net foreign direct investment inflow has a positive impact on real gross domestic product and per capita income. It indicates that increase in net foreign direct investment inflow leads to increase in real gross domestic product and per capita income of Nepal.